Krisis Self-Efficacy dan Prokrastinasi Akademik Remaja Perkotaan: Studi Kuantitatif pada Siswa - Fitriashka Nafila, Mecca; Miksaldi, Miksaldi; Sahgianor, Sahgianor; Surawan, Surawan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
This study aims to analyze the relationship between self-efficacy and academic procrastination in adolescents in urban environments. Using a quantitative correlational approach, this study involved 41 students of State Islamic Senior High Schools in Palangka Raya City as respondents selected through a simple random sampling technique. Data were collected using a self-efficacy scale and an academic procrastination scale, then analyzed using the Pearson Product Moment correlation technique. The results of the analysis showed a significant negative relationship between self-efficacy and academic procrastination, indicating that the higher the students' self-confidence, the lower their tendency to procrastinate academic tasks. The conclusion of the study confirms that strengthening self-efficacy is an important factor in reducing academic procrastination in students in urban areas.